Краденое солнце: [стихи : для детей дошкольного возраста] / Корней Чуковский - Чуковский Корней Иванович (Фламинго, 2017)
Экземпляры: ФО-8 (20171130) / Инвентарный номер: 51006z1 / Цена: / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос-Рус)6